PERILAKU TERENCANA KNOWLEDGE SHARING - Nur Wening (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2016)
University is a collector of knowledge has a role in supporting the concept of knowledge based economy. This study was conducted with subjects research university lecturers in Kopertis Wilayah V Yogyakarta were 300 respondents. The purpose of the study to examine the factors that influence knowledge sharing from the perspective of the theory oh human behavior and the Theory of Planned Behavior developed a research model of knowledge sharing. Using SEM analysis tool to test the research hypothesis. The results of the study with a response rate of 67% stated that the attitude toward knowledge sharing (BH.ATI) affects yhe intention to knowledge sharing (IKS), in addition to the influence of subjective norm (SN) on the intention to knowledge sharing. The test results also suggested taht hypothesis of planned behavior control (PBC) effect on the intention to knowledge sharing (IKS) prove to be significant. The results of the influence of planeed behavior controll (PBC) to the knowledge haring behavior (KSB) is not acceptable (H4 unsupport). In this case it is possible to make a faculty experience less or does not have a positive attitude to knowledge sharing with others. It’s because there is perception that some of the behavior he will gain certain advantages. Statement of intent to knowledge sharing (IKS) affect knowledge sharing behavior (KSB) is acceptable.